The Venetian takeover of the Margraviate of Istria (1411–1421) the modality of a passage : (with eight previously unedited documents in the Appendix) - Banić, Josip, povjesničar (2019)
The paper analyzes the incorporation of the Aquileian Margraviate of Istria into the expanding Venetian state in the first half of the fifteenth century. By analyzing this modality of a passage and comparing it to the integration formulae Venice employed in the rest of the Patriarchate of Aquileia, the author uncovers similarities and contrasts between the two models of incorporation. It is argued that Aquileian communities in Istria underwent a remodeling of communal institutions in order to mirror the salient administrative aspects of other Venetian subject centers on the Peninsula. This process, dubbed regional homogenization, did not take place throughout Aquileian Friuli. Finally, the paper deals with instances of negotiations between the newly annexed Istrian communities and the central government in Venice, demonstrating that this interplay resulted in re-negotiated governmental hierarchies that benefitted both the state’s capital and the subject centers.
Appendix na str. 64-71.
Bibliografske bilješke uz tekst ; bibliografija i izvori: 95 jed.
Summary.
Keywords: Regionalna uprava -- Povijest; Akvilejski patrijarhat; 15. st; Istra -- Venecija